2020
DOI: 10.1186/s41074-020-00064-w
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-labelling-aided semantic segmentation on sparsely annotated 3D point clouds

Abstract: Manually labelling point cloud scenes for use as training data in machine learning applications is a time- and labour-intensive task. In this paper, we aim to reduce the effort associated with learning semantic segmentation tasks by introducing a semi-supervised method that operates on scenes with only a small number of labelled points. For this task, we advocate the use of pseudo-labelling in combination with PointNet, a neural network architecture for point cloud classification and segmentation. We also intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Although a high threshold will result in more accurate pseudo-labels, it will lead to a decrease in the number of labeled points. However, Yao et al (2020) found that the experimental results are not sensitive to the threshold setting. Unlike using a fixed value, we developed an adaptive threshold-setting method.…”
Section: Generation Of Pseudo-labelsmentioning
confidence: 93%
See 2 more Smart Citations
“…Although a high threshold will result in more accurate pseudo-labels, it will lead to a decrease in the number of labeled points. However, Yao et al (2020) found that the experimental results are not sensitive to the threshold setting. Unlike using a fixed value, we developed an adaptive threshold-setting method.…”
Section: Generation Of Pseudo-labelsmentioning
confidence: 93%
“…Unlike the setting in Yao et al (2020), the model that converges on the ground truth is used as the condition for updating pseudo labels. We believe that there are some errors in pseudo labels, particularly when the scene is complex, thus completely fitting pseudo-labels may result in error transmission.…”
Section: Update Of Pseudo Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A generative model via adversarial training approximates the actual data manifold. The adopted approach tries to distinguish the relationship between the unlabeled data and the already labelled data sample using intermediate feature representations in deep neural network [27]. In recent research [28,29] on person re-identification, an approach of multi-pseudo labels on the generated data was used to reduce the risk of overfitting.…”
Section: Pseudo-labellingmentioning
confidence: 99%
“…The first is label propagation, a typical technique to generate pseudo labels. Yao et al [26] combined pseudo labelling with PointNet and proposed a process that alternates between classification network training and label propagation to generate final semantic labelling. Nonetheless, this framework employs transductive learning, and the model's performance remains debatable.…”
Section: Generate Pseudo Labelsmentioning
confidence: 99%